Sex change in islamic jurisprudence (fiqh) UAE law - Hammad, Hamza Abed Al-Karim (Medicine, law & society, 2019)
This study elucidates the positions of Islamic jurisprudence (fiqh) and the laws of the United Arab Emirates (UAE) on transsexuals' surgery. Using comparative analysis, the author concluded that the UAE law does not specify a rule regarding for transsexuals, but does state that in situations where the law is silent, then fiqh should be refereed to. Fiqh prohibits it; thus, the law does as well.
Keywords: emirati legislation; islamic law; islamsko pravo; reassignment surgery; sexual switch; spol; transseksualci; transsexual